A Benchmarking Approach to the Progress of Green Materials and systems’ use in the UAE construction industry - Elgayar, Aly (2016)
Over the past decade, the United Arab Emirates (UAE) introduced several green regulatory guidelines, federal decrees, and a considerable number of environmentally friendly initiatives. Hence, the purpose of this paper is to investigate the top green materials and systems used currently in the UAE construction industry as per the new laws dictate as well as see if professionals are switching over to incorporate more green materials, systems, and/or designs.